Analysis of Primary School Teachers' Perceptions of Everyday Digital Literacy on Students' Social Interaction Patterns - Mahira, Riska; Hidayat, Otib Satibi; Marini, Arita (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to analyse primary school teachers' perceptions of everyday digital literacy and its influence on students' social interaction patterns, extending previous research that predominantly focused on digital literacy among teachers or students as separate populations in primary education settings. The study employed a quantitative approach involving 177 primary school teachers and 160 public primary school students in Banten Province, selected using simple random sampling. Data were collected through questionnaire-based surveys and analysed using SPSS and SmartPLS. The findings indicate that there are no significant differences in everyday digital literacy levels between male and female teachers. Teachers’ digital literacy, particularly in information and communication competencies, shows a significant influence on students’ social interaction patterns, mainly in shaping the interaction environment, emotional atmosphere, and leadership dynamics in the classroom. Overall, the results confirm that teachers’ everyday digital literacy plays a crucial role in supporting positive social interaction among primary school students, although its influence on empathetic aspects of interaction remains relatively limited.